(untitled) (Journal of Civil Engineering Researchers, 2024)
In this study, geopolymer concrete made from fly ash was utilized, with different proportions of cement (0%, 10%, and 20%) replacing fly ash to examine the influence of cement presence in geopolymer concrete. To increase tensile strength and impact resistance, 0.5 and 1 percent steel fibers were used. Adding 0.5 percent fibers improved compressive strength by 9 percent, and for 1 percent fibers, it was 26 percent. The tensile strength also significantly increased with the addition of fibers. Adding 0.5% fibers, on average, increased the tensile strength by 25%, with the increase being 34% for 1% fibers. It was also noted that substituting cement for fly ash had little effect on compressive strength, but replacing 10% cement could be considered as the optimal substitution level in terms of tensile strength in the samples. The test results for impact resistance indicated a significant effect of steel fibers on the number of impacts until the first crack appeared and the complete rupture of the samples. Adding fibers increased the resistance to complete rupture by 12 to 22 percent with 0.5 percent fibers, and between 49 to 64 percent for 1 percent fibers. Replacing 10 percent rubber crumbs improved the impact energy of concrete, increasing the energy until the first crack by 10 percent on average and the energy until complete rupture by 15 percent.